Typification and homotypic synonymy of the names published in Kalanchoe (Crassulaceae subfam. Kalanchooideae) by Raymond-Hamet and Henri Perrier de la Bâthie in the 1910s and in 1948 - Smith, Gideon F.; Shtein, Ronen (Phytotaxa, 2021)
The 25 names, mostly at the rank of species, which were jointly published by Raymond-Hamet (1890–1972) and Henri Perrier de la Bâthie (1873–1958) in Kalanchoe (Crassulaceae subfam. Kalanchooideae) between 1912 and 1915, with a final name appearing in 1948, are catalogued. The current taxonomic status of the taxa, to which these names are applied, is provided and where necessary the names are typified or previous typifications are corrected or superseded if these were not effective.